Updated Meta-analysis Reveals Limited Efficacy of Vitamin D Supplementation in Chronic Low Back Pain - LEE, TSAI-JEAN; TSAI, RU-YIN; HO, CHI-CHUNG; CHEN, CHIEN-MIN; LI, CHEN-PI (In vivo (Athens), 2024)
Chronic low back pain (CLBP) significantly reduces quality of life and increases reliance on healthcare resources. Despite many individuals opting for vitamin D supplementation to alleviate CLBP, its efficacy remains debatable. This meta-analysis aimed to evaluate the potential benefits of vitamin D supplementation in treating this condition. Adhering to PRISMA guidelines, we systematically reviewed the effectiveness of vitamin D supplementation in adults with CLBP, focusing exclusively on randomized controlled trials (RCTs). A comprehensive literature search was conducted up to May 2024 across multiple databases, including PubMed, Scopus, Cochrane Library, and Web of Science. Ten RCTs meeting our inclusion criteria were analyzed. The results indicated that vitamin D supplementation did not significantly reduce pain scores compared to control groups (SMD: -0.130, 95%CI=-0.260 to 0.000; I =0%), regardless of participants' baseline vitamin D levels. Moreover, long-term supplementation showed no notable improvement in CLBP outcomes (SMD: -0.097, 95%CI=-0.290 to -0.097; I =19.878%). Additionally, supplementation with active forms of vitamin D (SMD: -0.321, 95%CI=-0.670 to 0.028; I =0.000%) did not result in significant pain relief for chronic lower back pain. Vitamin D supplementation does not substantially alleviate CLBP. Nevertheless, it may still be considered as part of a comprehensive treatment plan. Further research is necessary to explore its long-term effects and the underlying mechanisms that may explain the observed lack of benefit.